2005
DOI: 10.1161/circulationaha.104.492108
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Improves Defibrillation Success and Resuscitation Outcomes From Ventricular Fibrillation

Abstract: Background-Induced hypothermia is recommended to improve neurological outcomes in unconscious survivors of out-of-hospital ventricular fibrillation (VF) cardiac arrest. Patients resuscitated from a VF arrest are at risk of refibrillation, but there are few data on the effects of already existing hypothermia on defibrillation and resuscitation. Methods and Results-Thirty-two swine (meanϮSE weight, 23.0Ϯ0.6 kg) were divided into 4 groups: normothermia (nϭ8), mild hypothermia (35°C) (nϭ8), moderate hypothermia (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 32 publications
1
70
0
5
Order By: Relevance
“…Using a porcine model of VF cardiac arrest (no-flow) of 8 min, Boddicker et al showed that pre-existing hypothermia of 30°C or 33°C facilitated significantly improved resuscitation outcomes in comparison with normothermic resuscitation, but that a temperature of 35°C was not beneficial to the resuscitation outcome. 30 Wu et al showed that profound hypothermia (10-15°C for 1 h), followed by mild hypothermia (34°C for 36 h) produced a better intact survival rate than normothermic resuscitation or profound hypothermia (10-15°C for 1 h), followed by mild hypothermia (34°C for 12 h) in a canine model of hemorrhagic cardiac arrest. 31 Gunn et al reported that delayed onset brain edema following 30 min of cerebral ischemia was abolished by prolonged (3-day) hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Using a porcine model of VF cardiac arrest (no-flow) of 8 min, Boddicker et al showed that pre-existing hypothermia of 30°C or 33°C facilitated significantly improved resuscitation outcomes in comparison with normothermic resuscitation, but that a temperature of 35°C was not beneficial to the resuscitation outcome. 30 Wu et al showed that profound hypothermia (10-15°C for 1 h), followed by mild hypothermia (34°C for 36 h) produced a better intact survival rate than normothermic resuscitation or profound hypothermia (10-15°C for 1 h), followed by mild hypothermia (34°C for 12 h) in a canine model of hemorrhagic cardiac arrest. 31 Gunn et al reported that delayed onset brain edema following 30 min of cerebral ischemia was abolished by prolonged (3-day) hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…subjected to defibrillation shocks and cardiopulmonary resuscitation following unsupported VF, Boddicker et al (3) showed that the defibrillation success and subsequent resuscitation outcome were improved by preexisting MH and SH, and the effect was most remarkable at MH. Some unidentified mechanical, metabolic, or electrophysiological properties were suggested to be involved in the beneficial effect of hypothermia in terms of prevention of refibrillation (3). In the present study, a certain modification of SW dynamics at MH could contribute to the in vivo prevention of refibrillation following DC shocks.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to recent guideline recommendations that all unconscious adult patients with spontaneous circulation after out-of-hospital cardiac arrest should be cooled to 32-34°C for 12-24 h when the initial rhythm was VF (1). In experiments using swines with induced VF, Boddicker et al (3) demonstrated that defibrillation success of electrical shocks and resuscitation outcomes were significantly improved under moderate hypothermia (MH, 33°C) compared with normothermia (NR, 37°C) and that the benefit of MH was larger than severe hypothermia (SH, 30°C) (3). The underlying mechanisms of this amelioration are not well understood.…”
mentioning
confidence: 99%
“…Taken together, it is possible that the hypothermia related reduction in t-PA release during ischemia/reperfusion may contribute to the tissue protective effects of hypothermia. It may also be part of the explanation to why hypothermia has been found to increase defibrillation success and resuscitation outcome at cardiac arrest in a porcine model [48].…”
Section: Discussionmentioning
confidence: 99%